Congenital malaria: Importance of diagnosis and treatment in pregnancy - Gülaşı, Selvi; Özdener, Nureddin (The Turkish Journal of Pediatrics, 2016)
Congenital malaria, in which infants are directly infected with malaria parasites from their mother prior to or during birth, is a potentially life-threatening condition that occurs at relatively low rates in malaria endemic regions. We report an unusual case of a 23-day-old girl with neonatal Plasmodium vivax malaria, suspected primarily on the basis of positive maternal history that her mother had malaria during her pregnancy and was cured with chloroquine therapy. Infant presented with fever, thrombocytopenia and a significant parasitemia. She responded to chloroquine antimalarial therapy and was discharged successfully 10 days after admission. We emphasize the importance of diagnosis and treatment in pregnancy and follow-up with these newborns after birth by neonatologists and pediatric specialists.